DASAR WAJIB MEMATUHI UNDANG-UNDANG PERKAWINAN DAN KHI - Nelli Fauziah; M. Abdul Hakim (Tim Jurnal STAI KH. Zainuddin Ponpes Mojosari, 2023)
The Marriage Law (UUP) and KHI are legal products authorized by the Indonesian government. As a country of law, the Indonesian people are obliged to obey it. But in reality, there are still many people who ignore the applicable laws and assume that the UUP and KHI are only rules from the state, not sharia from Allah SWT that must be obeyed. This paper aims to prove the obligation to comply with the UUP and KHI. This research includes library research with data collection methods from primary data in the form of the UUP and KHI itself, the nash Al-Qur'an and hadith which are the basis for the obligation to obey ulil amri, then collect secondary data on related studies from books, journals, and other supporting sources. While the approach used is a socio-legal approach with data analysis methods in the form of descriptive analytics. The purpose of writing this article is to analyze the process of forming laws in Islam, UUP and KHI, parse family law issues in UUP and KHI that are different from classical fiqh, describe the urgency of legal change in the theory of law is a tool of social engineering, and describe the basis for compulsory compliance with UUP and KHI. The results of this study prove that the basis for the obligation to obey the Marriage Law and KHI is the same as the basis for the obligation to obey the Qur'an, Sunnah, and ulil amri, because both are products of government ijtihad (ulil amri). Government ijtihad is a manifestation of collective ijma', which is the result of the thoughts and agreements of leaders (umara>), scholars, Muslim jurists and scholars, practitioners and academics who are experts in their fields. So that the obligation to obey the UUP and KHI can be said not to conflict with sharia and in line with the aim of achieving the benefit of society.